2018
DOI: 10.1111/bph.14448
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic effects of ASP3662, a novel 11β‐hydroxysteroid dehydrogenase 1 inhibitor, in rat models of neuropathic and dysfunctional pain

Abstract: ASP3662 is a potent, selective and CNS-penetrable inhibitor of 11β-HSD1. The effects of ASP3662 suggest that selective inhibition of 11β-HSD1 may be an attractive approach for the treatment of neuropathic and dysfunctional pain, as observed in fibromyalgia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…ASP8477 (inhibitor of fatty acid amide hydrolase) reduces evoked pain phenotype (muscle HA), being consistent with a previous study which demonstrates that ASP8477 elevates the anandamide (endogenous cannabinoid) concentration in both plasma and brain and attenuates evoked pain phenotype in animal models of neuropathic and chronic inflammatory pain (Watabiki et al, 2017) (Russell et al, 2011). ASP3662 (inhibitor of 11β-hydroxysteroid dehydrogenase [HSD]) reduces muscle HA, being consistent with its analgesic effect in animal models of neuropathic pain (Kiso et al, 2018b) and the evidence that intrathecal injection of glucocorticoid-R antagonist attenuates MA and heat HA in an animal model of neuropathic pain (Wang et al, 2004). Given that 11β-HSD1 is an enzyme responsible for the intracellular regeneration of glucocorticoids also in the CNS (Moisan et al, 1990), the reduction of active glucocorticoid in the CNS could be a mechanism for analgesic action of ASP3662.…”
Section: Possible Therapeutic Approaches To Nociplastic Painsupporting
confidence: 88%
“…ASP8477 (inhibitor of fatty acid amide hydrolase) reduces evoked pain phenotype (muscle HA), being consistent with a previous study which demonstrates that ASP8477 elevates the anandamide (endogenous cannabinoid) concentration in both plasma and brain and attenuates evoked pain phenotype in animal models of neuropathic and chronic inflammatory pain (Watabiki et al, 2017) (Russell et al, 2011). ASP3662 (inhibitor of 11β-hydroxysteroid dehydrogenase [HSD]) reduces muscle HA, being consistent with its analgesic effect in animal models of neuropathic pain (Kiso et al, 2018b) and the evidence that intrathecal injection of glucocorticoid-R antagonist attenuates MA and heat HA in an animal model of neuropathic pain (Wang et al, 2004). Given that 11β-HSD1 is an enzyme responsible for the intracellular regeneration of glucocorticoids also in the CNS (Moisan et al, 1990), the reduction of active glucocorticoid in the CNS could be a mechanism for analgesic action of ASP3662.…”
Section: Possible Therapeutic Approaches To Nociplastic Painsupporting
confidence: 88%
“…Preclinical studies in rats have shown that ASP3662 has significant analgesic effects in a number of models of neuropathic and dysfunctional pain. 4 Furthermore, conditions characterized by altered glucocorticoid homeostasis, such as agitation associated with Alzheimer's disease, may also benefit from this mechanism. 5,6 To date, several selective and nonselective 11β-HSD1 inhibitors have been developed for indications such as type 2 diabetes mellitus and metabolic syndrome (e.g., RO5093151, RO5027383, MK-0916, and INCB13739), [7][8][9] nonalcoholic fatty liver disease (e.g., RO5093151), 10 hypertension, and obesity (e.g., MK-0736 and AMG 221), 11,12 and Alzheimer's disease (ABT-384), 13 with limited success in part due to modest efficacy when compared with standard of care.…”
Section: Study Highlightsmentioning
confidence: 99%
“…ASP3662 has high affinity ( K i 5.3 nM) and competitive binding for human 11β‐HSD1 and demonstrates no inhibition of 11β‐HSD2 at concentrations < 3,000 nM (Internal study reports 3662‐PH‐0001 and 3662‐PH‐0001‐0004). Preclinical studies in rats have shown that ASP3662 has significant analgesic effects in a number of models of neuropathic and dysfunctional pain . Furthermore, conditions characterized by altered glucocorticoid homeostasis, such as agitation associated with Alzheimer's disease, may also benefit from this mechanism .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A Positron Emission Tomography (PET) radiotracer targeting the 11β-HSD1 would allow for noninvasive imaging of the enzyme in vivo to better understand its expression under normal and pathological states. PET imaging is also invaluable in evaluating the target occupancy and efficacy of novel 11β-HSD1 inhibitors in many clinical trials, such as ABT-384, , UE-2343, PF-915275, MK0916, BMS-770767, and ASP3662 (Figure ).…”
Section: Introductionmentioning
confidence: 99%